Neuroendoscopic followed by microsurgical approach for the treatment of pilocytic astrocytoma of the pineal region - Leopoldo Mandic Furtado; José Aloysio da Costa Val Filho; François Dantas; Camila Moura de Sousa (Brazilian Society for Pediatric Neurosurgery, 2021)
Pilocytic astrocytoma is a low-grade tumor that can affect the pineal region and has a potential life-threatening presentation with obstructive hydrocephalus. This video presents the case of a child who underwent an endoscopic third ventriculostomy with tumor biopsy and for whom a supracerebellar infratentorial approach was chosen after confirmation of the diagnosis of a pilocytic astrocytoma. Herein, we discuss the technical details of both procedures, such as the single burr hole in the neuroendoscopic approach, the ventricular landmarks and identification of the venous sinus through neuronavigation, the anatomical landmarks during the supracerebellar infratentorial approach, and the use of ultrasonographic aspiration.